Investigation of sound radiation by cantilever beam - Zaporozhets, Оlexander; Tokarev, Vadim; Hufenbach, Werner; Taeger, Olaf; Modler, Niels; Dannemann, Martin; Makarenko, Vitaly (Proceedings of National Aviation University (archive), 2006)
The research investigates vibration of a cantilever beam loaded with actuators and load. The equation of motion is based on Bernoulli-Euler-Timoshenko theory of beams with corresponding boundary conditions. This equation is solved by the method of Green functions. A feature of this investigation is taking into account the influence of concentrated force parameters, namely the value, location of actuator and phase difference between load and actuator. In the work represented the contribution of actuator parameters on total sound power level as well as on each mode separately.